Effect of Wetland Restoration and Degradation on Nutrient Trade-Off of Carex schmidtii - Zhang, Dongjie; Xia, Jiangbao; Sun, Jingkuan; Dong, Kaikai; Shao, Pengshuai; Wang, Xuehong; Tong, Shouzheng (Frontiers in Ecology and Evolution, 2022)
Plant nutrient trade-off, a growth strategy, regulates nutrient stoichiometry, allocation and stoichiometric relationships, which is essential in revealing the stoichiometric mechanism of wetland plants under environmental fluctuations. Nonetheless, how wetland restoration and degradation affect nutrient trade-off of wetland plants was still unclear. In this study, field experiments were conducted to explore the dynamic of nutrient stoichiometry and nutrient limitation of Carex schmidtii under wetland restoration and degradation. Plant nutrient stoichiometry and stoichiometric relationships among natural (NW), restored (RW), and degraded (DW) tussock wetlands were examined. Results showed that nutrient stoichiometry of C. schmidtii was partly affected by wetland restoration and degradation but varied among growth stages. The N:P and N:K ratios indicated N-limitation for the growth of C. schmidtii. Robust stoichiometric scaling relationships were quantified between some plant nutrient concentrations and their ratios of C. schmidtii. Some N- and P-related scaling exponents are varied among NW, RW, and DW. PCA indicated that wetland restoration and degradation had significantly affected on the nutrient trade-offs of C. schmidtii (May~August). Compared to NW, nutrient trade-off in RW was more similar to DW. Carex schmidtii had significant correlation between most nutrients and their ratios, and the SEM indicated that plant P and K concentrations had a high proportional contribution to plant C and N concentrations. Insights into these aspects are expected to contribute to a better understanding of nutrient trade-off of C. schmidtii under wetland restoration and degradation, providing invaluable information for the protection of C. schmidtii tussock wetlands.